Therapeutic effect of honey on acute respiratory infections in adults - Ahmed Ouaamr; Mouna Mekkaoui; El Hassane Ouaalaya; Aziz Mengad; Yahya Cherrah; Katim Alaoui (GarVal Editorial Ltda., 2024)
Context: In Morocco, acute respiratory infections (ARI) are a frequent cause of consultations in the first level health facilities. Scientific reports indicate that honey has an important biochemical therapeutic activity. Aims: To explore the therapeutic effect of honey on ARI in the Guelmim region of southern Morocco. Methods: This was a prospective clinical study aiming to compare the therapeutic effect of honey in the population that consumes it versus a control population, at the level of the regional hospital and health centers, the period of the study was between September 2022 and March 2023, All the participants were questioned through a questionnaire and the study of their files and monitoring forms. Results: The study population was divided into two equal groups of 417 people each. Honey significantly reduced the overall symptom score at Day 5 (p<0.001) in the honey group compared with the reference group, according to the ANOVA test, the significant variables are age, presence of associated diseases, duration of illness, number of consultations for respiratory episodes and current smoking status, the present study also shows that non consumption of honey OR = 15.09 [10.26-22.17], high symptom score at D1 OR = 3.85 [2.37-5.39], frequency of nocturnal cough OR = 4.26 [1.65-10.9], frequency of diurnal cough OR = 3.34 [1.5-7.4], duration of illness OR = 7.12 [3.4-14.6] and type of cough OR = 1.5 [1.04-2.2] were the determinants of high symptom score at Day 5. Conclusions: Honey was effective in relieving symptoms associated with ARI and may be suggested as an adjuvant treatment in adults.